Homalomena coerulescens Jungh. (Araceae) - A new angiospermic record for Bangladesh - Ara, Hosne; Uddin, Sarder Nasir; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 81-84, 2003 (December)